Production and characterization of granules from agricultural wastes and comparison of combustion and emission results with wood based fuels. (15th November 2019) - Chen, Haili; Forbes, E.G.A.; Archer, J.; De Priall, O.; Allen, M.; Johnston, C.; Rooney, D.
Highlights: Drum granulation was used to produce bio-waste granules with excellent flowability. The combustion properties of the fuels were compared in a 50 kW multi-fuel boiler. Gaseous emissions showed significant difference among different fuels. The produced granules BWG 1 and BWG 5 could be used as potential fuels. Abstract: As interests in using agricultural bio-waste to generate heat and energy are increasing, more information is needed on their suitability for production as potential bio-waste fuels. This is due largely to uncertainty regarding their physico-chemical properties, combustion potential and emissions profiles. The study described in this paper focused on the granulation of agricultural bio-waste and its performance as a solid biofuel during the combustion process in comparison with two standard wood fuels. It was observed that the granular bio-waste fuels had excellent flowability during the combustion process. Large variations were found in mineral concentrations, energy value, ash content and ash melting point between the fuels. Combustion tests in a 50 kW multi-fuel boiler revealed significant differences in flame temperature, boiler net efficiency and some gaseous emissions such as CO, CO2 and NO between different bio-waste fuels and wood fuels. The cow slurry and grass silage digestate based granular fuel produced the highest boiler temperature, followed by the granules made by the chicken litter and digestate mixed with wood waste. It was concluded that these granular bio-waste fuels met the energetic requirement for biomass fuels though combustion performance and flue gas emissions might raise issues.